Building smart cities, the just way. A critical review of "smart" and "just" initiatives in Bristol, UK. (May 2019) - Michalec, Aleksandra (Ola); Hayes, Enda; Longhurst, James
Highlights: Our analysis shows how practitioners embed climate justice in urban smart initiatives. Discourse analysis helped to reveal the explicit, implied and obscured aims of smart city initiatives. Our heuristic could improve traditional policy analysis assessments. Abstract: This article investigates the application of the "smart cities" and "urban climate justice" concepts to two urban initiatives based in Bristol, UK. Both ideas are increasingly popular in academic literature. Yet, little is known about their understanding by the practitioners such as policymakers, third sector organisations and citizens. Two case studies, a community-based energy efficiency initiative, and a local authority electric vehicle policy were critically reviewed using discourse analysis. The method helped to reveal the explicit, implied and obscured aims of the examined initiatives. Using discourse analysis, the researchers developed a heuristic which could improve traditional policy analysis approaches. The examination of case studies illustrates how practitioners understand the notions of "urban climate justice" and "smart cities" and whether their conceptualisations differ from those present in the academic literature. Finally, the paper offers methodological suggestions for embedding justice in "smart" initiatives at each stage of policy and project design.